First Year University Students Self-Reported Health Outcomes Over an Academic Semester - P.K., Doyle-Baker; K.M., Verge; L., McClelland; T., Fung (Journal of Behavior Therapy And Mental Health, 2018)
The transition to university can be a stressful time in a student’s life. Recent evidence demonstrates declining mental and physical health in college and university students compared to the general public. A prospective cohort study investigating mental and physical wellness over the course of a semester in a sample of first-year undergraduate students (N=74; 65%F) from nine faculties was completed at a large university in Canada. Sixty-eight (92%) students with a mean (SD, ±) age 18.2 ± 1.1 yrs., weight 67.9 ± 15.5 kg, height, 168.5 ± 11.6 cm and waist circumference 81.3 ± 9.8 cm completed the SF-36V2 quality of life questionnaire at the beginning and end of the semester in Fall 2014. A decrease in vitality (p=0.003), social functioning (p=0.004), emotional state (p=0.014), and mental health (p=0.019) outcomes as measured by the SF-36v2 occurred during the semester. In addition, aggregate mental health significantly declined from the beginning to the end of the semester (p <0.001), while physical health did not change (p=0.242). The importance of promoting and increasing awareness of campus wide mental health strategies should be considered a priority for first year undergrad students. Particularly, because students in their first year may take longer than one semester to adjust to the increased work load and although difficult to speculate it is possible that both mental and physical health would decline over the next (second) semester. Future research should aim for longer study duration.
Keywords: mental health; physical health; undergraduate students.